Delayed Pulmonary Apoptosis of Diet-Induced Obesity Mice following Escherichia coli Infection through the Mitochondrial Apoptotic Pathway. (22nd October 2019) - Wang, Fengyuan; Zuo, Zhicai; Yang, Zhuangzhi; Chen, Kejie; Fang, Jing; Cui, Hengmin; Shu, Gang; Zhou, Yi; Geng, Yi; Ouyang, Ping
Abstract : Escherichia coli ( E. coli ) is one of pathogens causing nosocomial pneumonia and could induce pulmonary excessive apoptosis. Although much has been learned about metabolic diseases induced by obesity, the information linking bacterial pneumonia to obesity is limited. Accordingly, we investigated the apoptosis of normal (lean) and diet-induced obesity (DIO, fed a high-fat diet) mice after nasal instillation with E. coli . Lung tissues were obtained at 0 (preinfection), 12, 24, and 72 h after infection, and acute pulmonary inflammation was observed at 12 h. Elevated cell apoptosis and percentage of pulmonary cells depolarized with collapse of the mitochondrial transmembrane potential ( Δψ m) occurred in response to bacterial infection. The relative mRNA and protein expressions of Bax, caspase-3, and caspase-9 increased, but Bcl-2 decreased in the lung. Interestingly, the apoptotic percentage and most of apoptosis-associated factors mentioned above peaked at 12 or 24 h in the lean- E. coli group, while at 24 or 72 h in the DIO- E. coli group. Taken together, these findings indicated that the E. coli pneumonia caused excessive pulmonary apoptosis through the mitochondria-mediated pathway, and the apoptosis was delayed in the DIO mice with E. coli pneumonia.